SIDEWALKS: THE PUBLIC SPHERE "PLUNDERED" BY ECONOMIC INTERESTS Study in Bandung City - Gunawan, Wawan (CosmoGov: Jurnal Ilmu Pemerintahan, 2025)
Sidewalks remain a significant issue in urban development, particularly in large cities in Indonesia, including Bandung. To date, sidewalk development in Bandung has not received sufficient attention. Sidewalks, as public spaces, are unable to fulfill their intended functions properly. Economic encroachment is the main cause, manifested in the proliferation of street vendors, illegal parking, numerous provider poles, billboards, and PLN electrical poles, all of which "plunder" public space intended for pedestrians. This study aims to examine how the Bandung city government manages sidewalks as public spaces from the perspective of good governance, focusing on transparency, participation, accountability, and law enforcement. Through a literature review approach, the study found that in sidewalk management, the Bandung city government has not fully met the principles of good governance. The city government lacks transparency, as evidenced by insufficient socialization about the function of sidewalks. In terms of participation, the public has not been adequately involved in sidewalk management, as shown by the uneven distribution of sidewalk development. Furthermore, law enforcement remains weak, with violators of sidewalk usage not facing strict penalties. As a result, the overall management of sidewalks as public spaces in Bandung is not adequately accountable.gb777